Design, Optimization, in vitro and in vivo Evaluation of Flurbiprofen Loaded Solid Lipid Nanoparticles (SLNs) Topical Gel - K, Keerthana; DS, Sandeep (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: The aim of present study was to carry out the formulation design and evaluation of Solid Lipid Nanoparticles (SLNs) loaded topical gel of Flurbiprofen. Materials and Methods: Flurbiprofen solid lipid nanoparticles (SLNs) were formulated using Glyceryl monostearate (GMS) as lipid matrix by solvent evaporation method followed by probe sonication. A 32 full factorial design was utilized to optimize the SLNs. Drug: lipid ratio and sonication time were chosen as independent variables. Particle size, entrapment efficiency (%) and PDI were dependent variables. The optimized Flurbiprofen SLNs was formulated as topical gel and screened for pH, spredability, drug content, viscosity, drug release study, TEM analysis and in vivo skin irritation studies. Results: The optimized SLNs-gel had particle size of 369.8 nm, entrapment efficiency of 70.66% and PDI of 0.241. The zeta potential was found to be -33.4 mV resembling the better stability. Drug release study showed sustained release pattern with maximum release of 96.78% up to 10 hr following Highuchi kinetics mechanism. TEM study revealed that formulation had particle size in the nano scale range. In vivo skin irritation study on wister rats proved that formulation didn’t had any signs of irritation. Conclusion: Based on the obtained results, the study concluded that SLNs based Flurbiprofen gel can be better and promising topical drug delivery approach.
Keywords: SLNs; DoE; Flurbiprofen; Particle size; Zeta Potential; In vitro drug release